2016
DOI: 10.3402/gha.v9.32962
|View full text |Cite
|
Sign up to set email alerts
|

Leprosy trends at a tertiary care hospital in Mumbai, India, from 2008 to 2015

Abstract: BackgroundLeprosy remains an important cause of preventable disabilities. After the advent of multidrug therapy, new leprosy cases have come down dramatically. Despite this achievement, India, which contributes 60% of the global leprosy burden, faces some challenges to eliminate the disease, including active transmission in the community and delayed diagnosis of leprosy patients.ObjectivesThe objectives of the study were 1) to determine sociodemographic and clinical characteristics of newly diagnosed adults an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 5 publications
(3 reference statements)
0
9
0
2
Order By: Relevance
“…Ceci se rapproche de l'âge moyen des patients dans une précédente étude à Lomé qui était de 35 ans. Muthuvel et al en Inde avait trouvé un âge moyen de 32 ans [6] et Keita [7] au Mali avait trouvé un âge moyen de 33,8 ans. Les nouveaux cas de lèpre au Togo sont donc plus fréquents chez l'adulte jeune.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Ceci se rapproche de l'âge moyen des patients dans une précédente étude à Lomé qui était de 35 ans. Muthuvel et al en Inde avait trouvé un âge moyen de 32 ans [6] et Keita [7] au Mali avait trouvé un âge moyen de 33,8 ans. Les nouveaux cas de lèpre au Togo sont donc plus fréquents chez l'adulte jeune.…”
Section: Discussionunclassified
“…Ce taux se rapproche des 6,4% [8]en 2014 au Brésil. Il reste cependant inférieur au 10% rapporté en 2015 en Inde [6] et 14% rapporté en 2002 au Sénégal [9]. Dans une précédente étude à Lomé la capitale, 6,4% des patients étaient âgé de moins de 15 ans.…”
Section: Discussionunclassified
“…Previous studies also observed leprosy to be more common in middle age. 2,3 Family history of leprosy was in 1.5% of our patients. Chhabra et al observed similar history in 5.9% patients.…”
Section: Discussionmentioning
confidence: 99%
“…10% of new patients were children in a study from Mumbai during 2008-2015. 2 In another ten-year retrospective study (2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012) from Kerala, 12.1% of new leprosy cases were in children. 5 Most of our patients presented in 4 th and 5 th decade of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation